Mr pink-whistle's party - Blyton, Enid; Kimber, Kevin (Award Publications Worksop, England, 2014)
Mr. Pink-Whistle's Party is a charming children's story about a magical little man, Mr. Pink-Whistle, who uses his powers to bring joy and justice, throwing a special party for those in need of cheer.